Crystal analysis of grain boundaries in boron-doped diamond superconducting quantum interference devices operating above liquid helium temperature. (30th August 2021) - Morishita, Aoi; Amano, Shotaro; Tsuyuzaki, Ikuto; Kageura, Taisuke; Takahashi, Yasuhiro; Tachiki, Minoru; Ooi, Shuuichi; Takano, Miwako; Arisawa, Shunichi; Takano, Yoshihiko; Kawarada, Hiroshi
Abstract: Superconducting quantum interference devices (SQUIDs) are magnetometers with ultra-high sensitivity that have garnered attention owing to their potential application in flux qubits for quantum computing. The Josephson junction is an important component that determines the characteristics of a SQUID. Based on the superconductivity of heavily boron-doped diamond (111) homoepitaxial layers with a high critical temperature ( T c  > 10 K), we propose two types of Josephson junction structures with discontinuous (111) boundaries. These structures allow the SQUID to operate above liquid helium temperature (4.2 K) with high reproducibility. We analyzed local misorientation and strain (i.e., compressive, tensile, and shear strain) at the boundary via electron backscatter diffraction. The Josephson junction characteristics were attributed to the weak link with discontinuous boundaries of diamond (111) sectors. Graphical abstract: Image 1 Highlights: Josephson junctions and SQUIDs with only a diamond (111) sector are fabricated. SQUID operation above liquid helium temperature (4.2 K) is demonstrated. Magnetic field sensitivity increases for narrower strips with larger effective area. Locational misorientation and distortion are important for Josephson Junctions. Josephson junctions with steps rising toward the [211] direction work well.